The Issue of Securing the Stability of the Parliament in the System of Parliamentary Governance of the RA - Stepanyan , V. (Bulletin of Yerevan University C: Jurisprudence, 2017)
The shift from the quasi-presidential government to a parliamentary one through the 2015 amendments to the Constitution raised the issue of securing the parliamentary majority, and thus, the issue of securing the stability of the parliamentary government. The text of the amended Constitution, however, lacks any provisions that would act to provide such stability. As such, the Constitution only provides for a blanket provision (article 89, section 3) which states: “the Electoral Code guarantees formation of stable parliamentary majority.” However, the Electoral Code can only guarantee the formation of the parliamentary majority, but not the stability of the latter one. The issue 10 of stability arises throughout the course of operation of the parliament, and thus, is outside the scope of the regulation of the Electoral Code. Further, one must also take into the account that the possibility of any statutory regulation of public intercourse in this field is severely limited. The level of the parliamentary stability is conditioned primarily by objective factors, the existence of which is highly questionable in the Republic of Armenia.
Keywords: Form of state governance, parliamentary governance, parliamentary majority, Constitution, political stability